Elucidating the catalytic effect of metal ions in montmorillonite on thermal degradation of organic modifier - Zope, Indraneel Suhas (2017)
A key parameter influencing ignition, heat of combustion and charring of polymer/clay (montmorillonite, MMT) nanocomposites during combustion is the catalytic activity of clay. This work explores the effect of metal ions (MIs) like Mg2+, Al3+ and Fe3+ that are inherent to clay in altering the kinetics of degradation of organic modifier, hexadecyltrimethylammonium bromide (HDTMA-Br). Based on Brønsted and Lewis acid characteristics associated with these metal ions, their catalytic activity varied; Brønsted acidity affected initial stages of organic modifier degradation, while Lewis acidity influenced oxidation stability of carbonaceous residue beyond dehydration temperatures. For example, OMgMMT yielded delayed peak degradation temperature for HDTMA+, while Fe3+ ions from OFeMMT significantly lowered the oxidation stability of carbonaceous content. Knowing the effect of each metal ion separately, correlation between clay structural chemistry and organic degradation onset has been established. Degradation mechanism for alkyl fragment (from organic modifier) was provided adding fundamental knowledge to the field that will help in the design and development of polymer/clay nanocomposites with superior fire retardancy.